Dental Caries Prevention Strategies, Application of Evidence-Based Medicine. Part I. Basic Documents, Global and European Initiatives - Z. Broukal; J. Dušková; V. Merglová; R. Koberová-Ivančaková; E. Ryšlavá (Czech Dental Chamber, 2015)
Background and aim: Summarizing series of overview articles intends to show current strategy to prevent tooth decay and contemporary transnational initiatives aimed mainly at controlling caries in children and youth. In the first part of this series is defined the problem of dental caries in its social and public health context, taking account of new diagnostic technologies and decision-making processes about his healing or restoration. It is emphasized here the application of the concept of evidence based medicine evaluating the results published in information resources in terms of their scientific quality and weight recommendations for clinical practice and their projections into the current dental literature. The aim of this review is to characterize the basic current trends in dental caries prevention and their implementation of into individual and community preventive practice.